Subsidence analysis in DKI Jakarta using Differential Interferometry Synthetic Aperture Radar (DInSAR) Method - Cyntia, Cyntia; Pudja, I Putu (Sustinere: Journal of Environment and Sustainability, 2018)
Land subsidence in DKI Jakarta influenced by several key factors, including the number of buildings that increase the load above the surface. There are still many people who explore groundwater sources as the principal source of clean water. Also,  the soil type is dominated by alluvial. This alluvial deposit can be one of the parameters for soil deformation in the form of land subsidence and uplift in land surface because basically, alluvial soil types have a susceptibility to the load support power above. So that the land subsidence in DKI Jakarta is relatively continuous. To find out the land subsidence is used a high-tech method,  Differential Interferometry Synthetic Aperture Radar (DInSAR) satellite image of radar data (SAR Sentinel-1A) in 2017. The result shows the land subsidence in the average value of DKI Jakarta which is about -3.685 cm/year and the highest subsidence happened in the West Jakarta district about -5.850 cm/year in average.